Characterisation of the flow past real road vehicles with blunt afterbodies. (1st January 2014) - Grandemange, Mathieu; Ricot, D.; Vartanian, C.; Ruiz, T.; Cadot, O.
The flows past two different road vehicles with blunt after-bodies are studied at Reynolds numbers 107. The boundary layer thickness and the pressure distribution around the body are characterised. Then, the wake is investigated through static pressure and velocity measurements. Similar properties are obtained for both vehicles; in particular the lowest pressure on the afterbody is reported on the lower part of the base. Hot-wire anemometry is also used to depict the dynamics of the flow. The detached shear from the roof behaves as free shear turbulent flows whereas the flow from the underbody rather corresponds to homogeneous shear turbulent flows. In addition, global mode dynamics is reported in the wake of one vehicle and is associated with an antisymmetric coupling of the lateral mixing layers. However, the intensity of this mode is limited and its maximum of amplitude is downstream of the recirculation bubble; therefore it may not be a contributor to the drag. Eventually, these results are analysed to orient future drag reduction control strategies.